Ephemeral income. (8th December 2021) - Barlow, Josh; Morrow, Guy
Abstract : There are two main types of income earned by musicians. The first is capital income, which is the type of income derived from owning the intellectual rights to music, either through record sales or leveraging moral rights. The second is labour income, which is generated from live performance and takes the form of performance fees. Historically, these two activities are considered separate with some ontological and economic interdependences, creating two different streams of income; however, we present a case which shows that the two merged when much 'live' music appeared online during the COVID-19 pandemic in the form of livestreams. These livestreams theoretically allow musicians to earn both capital income and labour income from the same activity. We use 'design culture', as a form of organizational culture, to describe how musicians can use the new livestreaming trend to realize better/fairer deals for themselves. This is especially prescient because in contemporary history, most musicians cannot earn a sustainable income from releasing recorded music, so have relied on live performance. Live performance has thus become less ephemeral, as has the income derived from it.